2012
DOI: 10.4238/2012.march.14.1
|View full text |Cite
|
Sign up to set email alerts
|

RT-qPCR assay on the vitamin D receptor gene in type 2 diabetes and hypertension patients in Turkey

Abstract: ABSTRACT. RT-qPCR was used to analyze the vitamin D receptor (VDR) gene TaqI polymorphism in 100 Turkish patients with type 2 diabetes mellitus (T2DM) and hypertension compared with 100 healthy subjects, to determine whether VDR could be considered as one of the susceptibility genes for T2DM and hypertension. Genotyping was done with PCR, followed by melting curve analysis with specific fluorescent hybridization probes. The results showed that distributions for TT, Tt and tt genotypes were 51, 46 and 3% in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Of these, 14 case–control studies examined the association of the ApaI rs7975232 (G > T) variant [ 3 , 18 30 ] (Table 1 ), 22 studies in 20 case–control papers examined the association of the BsmI rs1544410 (A > G) variant [ 18 , 22 , 23 , 27 39 ] (Table 2 ), 19 studies in 18 case–control studies examined the association of the Taq1rs731236 (T > C) variant[ 3 , 18 28 , 32 , 33 , 35 , 38 – 40 ] (Table 3 ) and 18 studies in 16 case–control studies in15 papers examined the association of FokIrs2228570 (C > T)variant [ 3 , 18 , 23 25 , 27 , 30 32 , 36 , 41 45 ] (Table 4 ) with Insulin resistance related diseases susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 14 case–control studies examined the association of the ApaI rs7975232 (G > T) variant [ 3 , 18 30 ] (Table 1 ), 22 studies in 20 case–control papers examined the association of the BsmI rs1544410 (A > G) variant [ 18 , 22 , 23 , 27 39 ] (Table 2 ), 19 studies in 18 case–control studies examined the association of the Taq1rs731236 (T > C) variant[ 3 , 18 28 , 32 , 33 , 35 , 38 – 40 ] (Table 3 ) and 18 studies in 16 case–control studies in15 papers examined the association of FokIrs2228570 (C > T)variant [ 3 , 18 , 23 25 , 27 , 30 32 , 36 , 41 45 ] (Table 4 ) with Insulin resistance related diseases susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…A second possibility is that vitamin D may play an insignificant role in the regulation of blood pressure. Vuralet al previously reported that there was no statistically significant difference in the genotype distributions and allele frequencies of the vitamin D receptor gene TaqI polymorphism between hypertensive patients and controls in Turkey (32). The largest randomized, double-blind, placebo-controlled trial (Women's Health Initiative, n=36,282) failed to demonstrate an impact of vitamin D supplementation on blood pressure or incident hypertension over a 7-year follow-up period (33).…”
Section: Discussionmentioning
confidence: 99%
“…VDR polymorphisms have been associated with type 1 DM (T1DM) [11] and T2DM [1315]. BsmI (A > G, rs1544410), ApaI (A > C, rs7975232), TaqI (T > C, rs731236), and FokI (C > T, rs2228570) are human VDR single-nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%